2023
DOI: 10.3389/fcvm.2023.1131962
|View full text |Cite
|
Sign up to set email alerts
|

Threshold values of brachial cuff-measured arterial stiffness indices determined by comparisons with the brachial–ankle pulse wave velocity: a cross-sectional study in the Chinese population

Abstract: BackgroundArterial Velocity-pulse Index (AVI) and Arterial Pressure-volume Index (API), measured by a brachial cuff, have been demonstrated to be indicative of arterial stiffness and correlated with the risk of cardiovascular events. However, the threshold values of AVI and API for screening increased arterial stiffness in the general population are yet to be established.MethodsThe study involved 860 subjects who underwent general physical examinations (M/F = 422/438, age 53.4 ± 12.7 years) and were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 63 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Arterial velocity-pulse index (AVI) and arterial pressure-volume index (API) are non-invasive indices for assessing arterial stiffness, which are noninvasively measured using a single brachial oscillometric cuff operating similarly to that used in blood pressure measurement [11,12]. Previous studies have extensively demonstrated the significant correlations between AVI and API and PWV in healthy individuals [11], which suggests that AVI and API hold the potential to serve as viable alternatives to PWV for assessing arterial stiffness [13]. The device used to measure AVI and API (i.e., Portable Arterial Pulse Wave Detector (PASESA AVE-2000 Pro, DAIWA Healthcare, Shenzhen, China) has been certificated and put on the market in China since 2016.…”
Section: Current Non-invasive Brachial Cuff-measured Indices Of Arter...mentioning
confidence: 99%
See 3 more Smart Citations
“…Arterial velocity-pulse index (AVI) and arterial pressure-volume index (API) are non-invasive indices for assessing arterial stiffness, which are noninvasively measured using a single brachial oscillometric cuff operating similarly to that used in blood pressure measurement [11,12]. Previous studies have extensively demonstrated the significant correlations between AVI and API and PWV in healthy individuals [11], which suggests that AVI and API hold the potential to serve as viable alternatives to PWV for assessing arterial stiffness [13]. The device used to measure AVI and API (i.e., Portable Arterial Pulse Wave Detector (PASESA AVE-2000 Pro, DAIWA Healthcare, Shenzhen, China) has been certificated and put on the market in China since 2016.…”
Section: Current Non-invasive Brachial Cuff-measured Indices Of Arter...mentioning
confidence: 99%
“…The measurement is easier to implement than traditional arterial stiffness measurements, requires less time, and is more comfortable in terms of postural requirements. These merits make the device wellsuited for wide use in clinical settings and large-scale community screening [13,14].…”
Section: Current Non-invasive Brachial Cuff-measured Indices Of Arter...mentioning
confidence: 99%
See 2 more Smart Citations